Gene signatures of autopsy lungs from obese patients with COVID-19. (August 2021) - Santos e Silva, Juan Carlo; Vasconcelos, Amanda Pereira; Noma, Isabella Harumi Yonehara; Noronha, Natália Yumi; Aquino, Rodrigo; Giddaluru, Jeevan; Durão, Luiz; Costa-Martins, André Guilherme; Schuch, Viviane; Moraes-Vieira, Pedro M.; Nakaya, Helder I.
Summary: Background & aims: Obesity is associated with low grade systemic inflammation and insulin resistance. Although metabolic and immunological changes may contribute to the increased risk for COVID-19 mortality in obese, little is known about the impact of obesity in the lungs of patients with COVID-19. Methods: We analyzed gene expression profiles of autopsy lungs of a cohort of 14 COVID-19 patients and 4 control individuals. Patients were divided into 3 groups according to their comorbidities: hypertension, type 2 diabetes (T2D) and obesity. We then identified the molecular alterations associated with these comorbidities in COVID-19 patients. Results: Patients with only hypertension showed higher levels of inflammatory genes and B-cell related genes when compared to those with T2D and obesity. However, the levels of IFN-gamma, IL22, and CD274 (a ligand that binds to receptor PD1) were higher in COVID-19 patients with T2D and obesity. Several metabolic- and immune-associated genes such as G6PD, LCK and IL10 were significantly induced in the lungs of the obese group. Conclusion: Our findings suggest that SARS-CoV-2 infection in the lungs may exacerbate the immune response and chronic condition in obese COVID-19 patients. Highlights: Body Mass index-correlated genes suggest the impact of immunometabolism in severe COVID-19. Expression of 15 metabolism and immune-related genes was exclusively induced in the lungs of obese COVID-19 patients. Metabolic changes and antiviral immunity may increase inflammation in obese COVID-19 patients.